Effect of surface treatment on interfacial shear strength of basalt fiber reinforced polypropylene composite - Zhou, Ying‐Guo; Liang, Teng‐Fei; Wu, Bu‐Yong (Polymer composites)
Basalt fiber‐reinforced polypropylene (BFPP) is an important composite for thermoplastic polymer materials with wide applications due to the strong mechanical properties and the ease of recycling, and the mechanical properties of the composites are highly dependent on the interfacial adhesion between the fibers and the matrices, especially for the foamed products. In this study, in order to enhance the interfacial adhesion between the BF and PP, a novel in situ treating technology, which was proved to modify rapidly the surface of BF, was proposed and used for fabricating the BFPP composite. After surface treatment by both a silane coupling agent and a self‐made sizing agent, BF exhibited an uneven surface with regular grooves, and the strong interfacial adhesion between BF and the PP matrix was achieved, leading to a highly enhanced interfacial shear strength (ISS) of 14.39 MPa. Hence, the tensile strength of BFPP solid and foamed samples were 53.64 and 50.48 MPa, which showed roughly 57.1% and 79.4% increase than that of untreated fiber‐reinforced solid and foamed PP, indicating the efficient reinforcing effect of BFs on PP solid and foamed composites. Moreover, the foamed BFPP parts are more sensitive to the ISS than the solid ones, which was attributed to the variation of the critical length resulting from the foamed cells. This work provided a facile method to fabricate enhanced BFPP composites with extraordinary application potential in the fields of industry, sports, and transportation. Highlights A novel processing method of the surface coating of BFs was proposed. The effect of interfacial bonding between fiber and matrix was verified. Sensitivity to interfacial shear strength between solid and foamed parts was different. Experimental schematic diagram and representative results of the process of BFPP.